On the movement of the honeybee queen in the hive - Jan Blaha; Martin Stefanec; Jiří Janota; Daniel Nicolas Hofstadler; Tomáš Rouček; Jiří Ulrich; Laurenz Alexander Fedotoff; George Broughton; Tomáš Vintr; Farshad Arvin; Thomas Schmickl; Tomáš Krajník (Scientific Reports)
Abstract A honeybee colony is a complex and dynamic system that emerges out of the interactions of thousands of individuals within a seemingly chaotic and heterogeneous environment. At the figurative core of this system is the honeybee queen, responsible for the growth and reproduction of the eusocial superorganism. In this study, we examine the interaction between the queen and her surrounding environment by analyzing her movement patterns using mathematical models and computational approaches. We employed a visual tracking system to observe three queens of Apis mellifera within their colonies over a three-week period and analyzed sets of quality tracklets to provide observational evidence regarding the queens’ motion-related decision-making. Contrary to expectations, we found that the queen’s short-term motion characteristics—such as speed and turning—were remarkably invariant across distinct hive regions, suggesting a lack of direct environmental modulation at short timescales. Yet, long-term patterns showed structured and strategic behavior. Inter-stop distances followed a power-law distribution, and queens repeatedly revisited specific spatial zones over multi-day timescales. These results indicate a dual-scale movement strategy that is not captured by standard random walk models, highlighting internal state or memory-based navigation. Our findings suggest that queen movement is shaped by temporally layered processes that may support brood nest stability, efficient egg-laying, and colony cohesion.